Fiscal Policy, Monetary Policy and Economic Growth in Indonesia - Retnowati, Diah; Purnomo, Sodik Dwi; Jati, Damar; Zumaeroh, Zumaeroh; Adhitya, Bagus; Fatmawati , Anisa; Kencana, Heris (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
Economic growth is still a measure of the success of policies made by the government. Indonesia, a developing country, needs the right policies to continue to encourage economic growth and rise from the crisis that has occurred. The economic crisis that occurred in 1998, 2008 and 2020 requires Indonesia to have the right fiscal and monetary policies to recover quickly. This study aims to analyze the effect of the impact of fiscal policy (taxes and government expenditure) and monetary policy (money supply, inflation, and exchange rate) on economic growth in Indonesia. The method used in this study is multiple linear regression with time series data from 1990 to 2020. The results of this study prove that tax revenue has a positive effect on economic growth in Indonesia. Meanwhile, government spending, inflation, money supply and exchange rates have a negative effect on economic growth in Indonesia. The implications of this study show that both monetary policy and fiscal policy should be made through in-depth study. The government must be able to increase tax revenue and spend state revenues on investment needs. Monetary policy must also be able to maintain low inflation and strengthen the exchange rate through trade and foreign exchange reserves.